Force production during maximal effort sprinting on the bend - Churchill, S.; Salo, A.; Trewartha, G.; Bezodis, I. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The force requirements of bend sprinting are not well understood. This study determined the forces produced and performance characteristics of seven male athletes during maximal effort sprinting on the bend and straight. There were asymmetrical changes in force production. Resultant force was reduced on the bend compared to the straight for the left step, but remained similar for the right step. Additionally, more mediolateral force was produced by the left step than the right step on the bend. Overall, we speculate that strength training should aim to meet the demands of bend running, although care should be taken to avoid introducing undesirable asymmetries into straight line sprinting.